2011
DOI: 10.1007/s00125-011-2163-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive investigation of kidney disease in type 1 diabetes by magnetic resonance imaging

Abstract: ) MRI were performed, before and during water diuresis. Contrast-enhanced MRI was performed at baseline urine flow rate. Renal artery flow, renal vascular resistance (RVR), cortical and medullary volumes, and R 2 * were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Assessment of kidney size and volume in the context of chronic kidney disease associated with cardiovascular risk profiles has been of long-standing interest with contradictory results [27][28][29][30][31]. In diabetic nephropathy pre-clinical studies show an increase of kidney volume even preceding hyperfiltrative stages [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of kidney size and volume in the context of chronic kidney disease associated with cardiovascular risk profiles has been of long-standing interest with contradictory results [27][28][29][30][31]. In diabetic nephropathy pre-clinical studies show an increase of kidney volume even preceding hyperfiltrative stages [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Intrarenal oxygenation can be assessed noninvasively in subjects with type 1 or type 2 diabetes by blood oxygenation level dependent magnetic resonance imaging (BOLD MRI) [1113]. Inoue et al, especially, demonstrated hypoxia in the renal parenchyma of chronic kidney disease (CKD) patients with or without diabetes, using diffusion-weighted (DW) MRI and BOLDMRI [13], and confirmed intrarenal hypoxia in patients with diabetes, suggesting that factors other than tubulointerstitial alteration (such as loss of peritubular capillaries) determine the degree of hypoxia in the renal cortex [13].…”
Section: Hypoxia In Diabetic Kidneymentioning
confidence: 99%
“…The BOLD-MRI technique itself has been criticized by some [40, 41], arguing that it is difficult to acquire the same anatomical slices in each participant when repeating the BOLD-MRI exams. However, the intraobserver variability of the cortical and medullary R 2* values is low when performed by an experienced investigator and when using a standardized breath-hold technique [42].…”
Section: Measurement Of Renal Tissue Oxygenation In Humans With Bomentioning
confidence: 99%